Understanding College Students' Acceptance of Cloud Classrooms in Flipped Instruction: Integrating UTAUT and Connected Classroom Climate. (January 2019) - Yang, Harrison H.; Feng, Lin; MacLeod, Jason
Cloud classrooms provide many advantages in higher education. However, little is known about the social influence of peer relationships on students' acceptance of cloud classrooms. This study utilized structural equation modeling to examine a model that integrates the Universal Theory of Acceptance and Use of Technology (UTAUT) and Connected Classroom Climate (CCC). Effort expectancy, social influence, and CCC were found to significantly impact cloud classroom acceptance by college students. Performance expectancy and facilitating conditions, however, did not affect acceptance. These findings contribute understanding that can support decision-making for the cloud classroom, with particular emphasis on increasing college students' acceptance and use of such technology. Administrators, researchers, and practitioners can use this knowledge to guide their implementation, improvement, and assessment of cloud classrooms. In addition, beyond the cloud classroom, our identification of this relationship between CCC and students' acceptance represents new knowledge to guide other contexts of online learning.